NIMS fatigue data sheet on gigacycle fatigue properties of A2017 (Al-4.0Cu-0.6Mg) aluminium alloy - Yoshiyuki Furuya; Hideaki Nishikawa; Hisashi Hirukawa (Science and Technology of Advanced Materials: Methods)
The new fatigue data sheets, Nos. 135 and 136, disclose the gigacycle fatigue properties of A2017-T4 aluminium alloys. No. 135 shows gigacycle fatigue test results at a stress ratio of R =  −1 up to 1010 cycles, obtained by rotating bending fatigue testing at 100 Hz and by ultrasonic fatigue testing at 20 kHz, together with the results obtained by uniaxial loading fatigue testing at 100 Hz up to 108 cycles. No. 136 details the results from high stress ratios obtained by ultrasonic fatigue testing and 100 Hz uniaxial loading fatigue testing. Many specimens failed at over 107 cycles, so conventional fatigue limits were not confirmed, while fatigue failures at over 109 cycles were very rare, suggesting that the fatigue limits are in the gigacycle region. The results of the three types of fatigue tests showed good agreement, indicating the frequency and the stress gradient effects to be negligible. The fatigue strength of the aluminium alloys was proportional to the tensile strength, similar to observations made with low-strength steels at 107 cycles, but lower, at 1010 cycles. The stress ratio effects, which reduced the fatigue strength in stress amplitudes, were not remarkable. The fatigue strengths at high stress ratios were close to the modified Goodman lines, meaning that the stress ratio effects could be estimated using conventional methods.